2023
DOI: 10.1155/2023/5746940
|View full text |Cite|
|
Sign up to set email alerts
|

The Identification and Clinical Value Evaluation of CYCS Related to Asthma through Bioinformatics Analysis and Functional Experiments

Abstract: Background. Asthma is one of the most common respiratory diseases and one of the largest burdens of health care resources across the world. This study is aimed at using bioinformatics methods to find effective clinical indicators for asthma and conducting experimental validation. Methods. We downloaded GSE64913 data and performed differentially expressed gene (DEG) screening. Weighted gene coexpression network analysis (WGCNA) on DEGs was applied to identify key module most associated with asthma for protein-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Mutations in ERBB2 promote PD-L1-mediated immune escape in gallbladder cancer 34 . CYCS is significantly associated with immune cells and promotes the proliferation of asthma cells in vitro 35 . Meanwhile, we also identified immune-related molecules by molecular prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in ERBB2 promote PD-L1-mediated immune escape in gallbladder cancer 34 . CYCS is significantly associated with immune cells and promotes the proliferation of asthma cells in vitro 35 . Meanwhile, we also identified immune-related molecules by molecular prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Yan Li et al conducted an analysis of DEGs in the GSE64913 dataset, and characterized the asthma-related traits within the same dataset. Their findings demonstrated that ANXA8, ATF4, CD44, CYCS, DDIT3, FKBP5, LDHA, PMAIP1, S100A2, and SFN exhibited potential as hub genes associated with asthma (Li et al 2023 ). Although the majority of their predicted genes demonstrated limited prognostic value when referencing the same dataset, this finding underscores the limited efficacy of hub gene characterization solely through the use of WGCNA.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%